Exploring long-run relationship and error correction of Thai output and price - Chancharoenchai, Kanokwan (Asian Journal of Applied Economics, 2016)
As the Thai economy has integrated into the world system, it increasingly endures not only internal circumstances, but also external turmoils. Stabilizing the country’s growth and inflation from macroeconomic shocks has then become a challenge to policymakers. This study thus concentrates on investigating the long-run relationship and the adjustment process towards the equilibrium of output and price of Thailand from 2001 to 2014. For this purpose, the dynamic relationship, cointegration property, and error correction term are explored by DOLS, various cointegration tests, and ECM. The cointegration test also remarks the possibility of monetary policymakers to surprise the market in order to expect the increase in output. It also reconfirms that the interest rate tends to be a passive monetary instrument in curbing inflationary. Moreover, the adjustment process to the long-run of both output and price is found to have a symmetric cointegration property which implies the systematic ECM. The symmetric error correction test presents the significantly negative elimination in the next quarter towards long term equilibrium. The monetary policymakers thus seem to react to the rise in inflation uncertainty by keeping down inflation. Meanwhile, the output level tends to have faster adjustment speed than that of the price level.